(untitled) (Latakia University Journal -Basic Sciences Series, 2021)
Let a real Hilbert space, , are maximal monotones operators and is locally Lipschitz continuous. The question is to find the zeroes of structured monotone operator . In this article we study the stability of Dynamical system in special situation when and when is convex, proper and lower-semi continuous, is convex and differential.